Is Postsecondary Education Affordable? - Baum, Sandy; Schwartz, Saul (International Higher Education, 2013)
The evolution of higher education from a privilege for the elite to an economic and social necessity for broad segments of the population has created financing challenges, along with new opportunities, for students and their families. Governments that were able to provide free or low-priced access to universities for the select few have found it necessary to charge rising levels of tuition, even as less-affluent citizens aspire to enroll. In a number of countries—including Canada, Chile, and England—students have taken to the streets to protest tuition policies. Students are less militant in the United States; but there, as elsewhere, rising college prices and stagnating incomes have led to the widespread perception that postsecondary education is “unaffordable” for more and more people. Yet, it is not obvious what “unaffordable” means. What price is relevant—the published price of postsecondary study, the price people actually pay, or the price people should be expected to pay? Efforts to increase educational opportunity can be hindered if policymakers do not have a clear idea of the meaning of an “affordable” or “unaffordable” education.